Engineering Tree Seasonal Cycles of Growth Through Chromatin Modification - Conde, Daniel; Perales, Mariano; Sreedasyam, Avinash; Tuskan, Gerald A.; Lloret, Alba; Badenes, María L.; González-Melendi, Pablo; Ríos, Gabino; Allona, Isabel (Frontiers in Plant Science, 2019)
In temperate and boreal regions, perennial trees arrest cell division in their meristematic tissues during winter dormancy until environmental conditions become appropriate for their renewed growth. Release from the dormant state requires exposure to a period of chilling temperatures similar to the vernalization required for flowering in Arabidopsis. Over the past decade, genomic DNA (gDNA) methylation and transcriptome studies have revealed signatures of chromatin regulation during active growth and winter dormancy. To date, only a few chromatin modification genes, as candidate regulators of these developmental stages, have been functionally characterized in trees. In this work, we summarize the major findings of the chromatin-remodeling role during growth-dormancy cycles and we explore the transcriptional profiling of vegetative apical bud and stem tissues during dormancy. Finally, we discus genetic strategies designed to improve the growth and quality of forest trees.